The life cycle assessment of trees outside woodlands: a systematic review of methodological approaches - Webb, Elsa; Burgess, Paul J.; Pexas, Georgios; McKnight, Curtis J. (Springer, 2025)
Purpose: The purpose of this study is to understand how Life Cycle Assessment (LCA) methodology has been applied to evaluate the impacts of trees outside woodlands and where improvements are needed. This review aims to discuss the primary limitations when using LCAs to assess trees outside woodlands, particularly in comparison to existing literature on their environmental, social, and economic implications. Methods: Following the established STARR-LCA systematic review protocol, a total of 102 studies across 30 countries were identified. The selected studies used LCA frameworks to assess the impacts of five different trees outside woodland systems. Qualitative data relating to the tree system and LCA methodology were manually extracted from each study and summarised for analysis based on the four phases of an LCA: goal and scope, life cycle inventory, impact assessment, and interpretation. Results and discussion: This review showed the selected studies were primarily located in Southern Europe, South America, and Asia. Orchards were the focus of 68% of the papers, followed by 13% assessing silvopastoral systems. No papers were found on hedgerows or Miyawaki forests, which were within the scope of this review. The most common functional units were based on mass, area, and economic measures, and 29% of studies used more than one functional unit to interpret their LCA results. Environmental impacts were considered in 98% of the selected studies, whereas 13% of studies integrated an economic impact assessment, and only 5% accounted for the social implications of trees outside woodlands. Similarly, even though trees outside woodlands can increase carbon sequestration and biodiversity levels, these measures were only incorporated into 25% and 10% of the LCA studies, respectively. Conclusions: The environmental, economic, and social impacts of trees outside woodlands are dependent on the type of system and its intended purpose, climatic zone, and landscape. Process-based LCAs can be used to effectively assess the impacts of trees outside woodlands. However, the ability to holistically assess trees outside woodlands is limited by current LCA methodology, particularly when accounting for system multifunctionality or ecosystem services such as carbon sequestration and biodiversity. To address these limitations, four research recommendations have been made to improve future LCA studies. This could enhance the usefulness of LCAs in understanding sustainability trade-offs and facilitating decision-making across different tree system scenarios.
Keywords: 33 Built Environment and Design; 15 Life on Land; Environmental Sciences; 3302 Building; 4011 Environmental engineering; 4016 Materials engineering; Life cycle assessment; Tree systems; Agroforestry; Orchard; Trees outside woodlands; Carbon sequestration; Multifunctionality; Systematic review